Report of simultaneous measles outbreaks in two different health regions in Portugal, February to May 2017 : lessons learnt and upcoming challenges - Augusto, Gonçalo Figueiredo (2019)
© This is an open-access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0) Licence. You may share and adapt the material, but must give appropriate credit to the source, provide a link to the licence, and indicate if changes were made. This article is copyright of the authors, 2019. This article is copyright of the authors or their affiliated institutions, 2019.